2017
DOI: 10.29312/remexca.v8i6.294
|View full text |Cite
|
Sign up to set email alerts
|

Respuesta de Phaseolus vulgaris a la salinidad generada por NaCl, Na2SO4 y NaHCO3

Abstract: Se evaluó en la etapa de germinación y plántula la respuesta a la salinidad inducida con NaCl, Na2SO4 y NaHCO3 de tres variedades de frijol que son las de mayor producción en Nayarit, México. En invernadero, se estableció un diseño experimental A×B×C completamente al azar con 63 tratamientos y cinco repeticiones. El factor A tuvo siete niveles de concentración de sal (de 0.000 a 5.760 g L-1), el B tres variedades de frijol (Negro, Pinto, Azufrado) y el C tres tipos de sal (NaCl, Na2SO4, NaHCO3). Se midió la ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
1
2
0
3
Order By: Relevance
“…The results obtained in this study agree with those reported by Can-Chulim et al (2017) who demonstrated that fresh and dry shoot biomass decrease of the common bean P. vulgaris is attributed to salinity stress that causes a reduction in water absorption. In this study, salinity caused by NaCl (75 mM) reduced fresh root biomass in 8.2%.…”
Section: Resultssupporting
confidence: 92%
“…The results obtained in this study agree with those reported by Can-Chulim et al (2017) who demonstrated that fresh and dry shoot biomass decrease of the common bean P. vulgaris is attributed to salinity stress that causes a reduction in water absorption. In this study, salinity caused by NaCl (75 mM) reduced fresh root biomass in 8.2%.…”
Section: Resultssupporting
confidence: 92%
“…Entre los diferentes niveles de NaCl se registró un decremento cuando las plantas fueron tratadas con 75mM de NaCl (Figura 1B), afectando la TC un 26.67% con respecto a las plantas que no recibieron estrés por salinidad (NaCl). Estos resultados coinciden con los reportados por Can-Chulim et al (2017), al estudiar el efecto de diferentes concentraciones de sales en tres variedades de frijol reportaron una disminución signif icativa del crecimiento cuando las plantas recibieron tratamiento de estrés salino de moderado (Conductividad eléctrica, [CE=2.3 dS m -1 ]) a severo (CE=9.0 dS m -1 ). Otros autores también reportaron una disminución de las variables evaluadas en frijol común, cuando las plantas Figura 1.…”
Section: Tasa De Crecimientounclassified
“…Among the most important fruit vegetables in cuisines worldwide is Phaseolus vulgaris L. This species is a formidable source of fibre, proteins and vitamins in most diets. Several authors have looked into its responses to unique stressors, for example how it responds to salinity stress (Taïbi et al, 2016;Can Chulim et al, 2017;Nadeem et al, 2019), or its responses to drought (Sadeghipour and Aghaei, 2012;Erhenhi, 2020) and waterlogging stress (Ntukamazina et al, 2017;Erhenhi, 2020) but few records exist on synergistic effects of these stressors on the species, as would be the case in natural cropping systems. The aim of this research was to investigate the ecophysiological responses of P. vulgaris to synergistic effects of salinity and irrigation regimes in screen house that mimic the predicted conditions.…”
Section: Introductionmentioning
confidence: 99%